Heterovalent-doping-enabled atom-displacement fluctuation leads to ultrahigh energy-storage density in AgNbO3-based multilayer capacitors - Zhu, Li-Feng; Deng, Shiqing; Zhao, Lei; Li, Gen; Wang, Qi; Li, Linhai; Yan, Yongke; Qi, He; Zhang, Bo-Ping; Chen, Jun; Li, Jing-Feng (Nature communications, 2023)
Dielectric capacitors with high energy storage performance are highly desired for next-generation advanced high/pulsed power capacitors that demand miniaturization and integration. However, the poor energy-storage density that results from the low breakdown strength, has been the major challenge for practical applications of dielectric capacitors. Herein, we propose a heterovalent-doping-enabled atom-displacement fluctuation strategy for the design of low-atom-displacements regions in the antiferroelectric matrix to achieve the increase in breakdown strength and enhancement of the energy-storage density for AgNbO 3 -based multilayer capacitors. An ultrahigh breakdown strength ~1450 kV·cm −1 is realized in the Sm 0.05 Ag 0.85 Nb 0.7 Ta 0.3 O 3 multilayer capacitors, especially with an ultrahigh U rec ~14 J·cm −3 , excellent η ~ 85% and P D,max ~ 102.84 MW·cm −3 , manifesting a breakthrough in the comprehensive energy storage performance for lead-free antiferroelectric capacitors. This work offers a good paradigm for improving the energy storage properties of antiferroelectric multilayer capacitors to meet the demanding requirements of advanced energy storage applications. AgNbO 3 has a potential for high power capacitors due to its antiferroelectric characteristics. Here, the authors achieve multilayer capacitors with energy-storage density of 14 J·cm −3 by heterovalent-doping-enabled atom-displacement fluctuation.